Syngas to light olefins conversion with high olefin/paraffin ratio using ZnCrO(x)/AlPO-18 bifunctional catalysts - Su, Junjie (Nat Commun, 2019)
Direct synthesis of light olefins from syngas (STO) using a bifunctional catalyst composed of oxide and zeolite has attracted extensive attention in both academia and industry. It is highly desirable to develop robust catalysts that could enhance the CO conversion while simultaneously maintain high selectivity to C2-C4 olefins. Herein, we report a bifunctional catalyst consisting of ZnCr binary oxide (ZnCrO(x)) and low-Si AlPO-18 zeolite, showing both satisfying selectivity to C2-C4 olefins of 45.0% (86.7%, CO(2) free) and high olefin/paraffin ratio of 29.9 at the CO conversion of 25.2% under mild reaction conditions (4.0 MPa, 390 °C). By optimizing the reaction conditions, the CO conversion could be markedly increased to 49.3% with a slight drop in selectivity. CD(3)CN/CO-FTIR characterizations and theoretical calculations demonstrate that low-Si AlPO-18 zeolite has lower acid strength, and is therefore less reactive toward the hydride transfer in the STO reaction, leading to a higher olefin/paraffin ratio.